Piezochromic properties of pyridil divinyl anthracene derivatives: a joint Raman and DFT study - Fernández-Palacios, Sara; Peña-Álvarez, Miriam; García Baonza, Valentín; Xu, Bin; Ma, Suqian; López-Navarrete, Juan Teodomiro; Moreno-Oliva, María; Ruiz-Delgado, María del Carmen (My University, 2017)
Piezochromic materials, which show color changes resulting from external pressure or mechanical grinding, are of great interest from a scientific viewpoint owing to their potential applications as pressure-sensing and optical-recording systems.[1] It has been recently discovered solid-state fluorescence properties and piezochromic luminescence in a family of 9,10-Bis((E)-n-(pyrid-2-yl)vinyl)anthracene, BPnVA (n=2 orto-,3 metha- and 4 para-) compounds, see Figure 1.[2] The crystal structures indicate that the three compounds with varying position of the nitrogen on the external pyridyl exhibit different molecular packing modes. In this work, we aim at providing further insight into the interplay played by the molecular and supramolecular structural changes and the luminescence changes observed under pressure by using a combined experimental-theoretical approach that links Raman spectroscopy with DFT calculations.
Keywords: Compuestos aromáticos; Compuestos π-conjugados; Piezocromismo; Raman; DFT